The deleterious effects of sofosbuvir and ribavirin (antiviral drugs against hepatitis C virus) on different body systems in male albino rats regarding reproductive, hematological, biochemical, hepatic, and renal profiles and histopathological changes - Ali, Rana A.; Awadalla, Eatemad A.; Amin, Yahia A.; Fouad, Samer S.; Ahmed, Maha Abd-El Baki; Hassan, Mohammed H.; Abdel-Kahaar, Emaad; Abdel-Aziz, Rehab H. (Scientific reports, 2024)
Sofosbuvir is one of the crucial drugs used in the treatment of chronic hepatitis C virus (HCV) in adults and children with compensated liver disease, including cirrhosis. It may be used alone or with other drugs. Ribavirin is an antiviral medication used to treat HCV infection. It is not effective when used alone and must be used in combination with other medications, such as sofosbuvir. This study pertains to a comprehensive assessment of the deleterious effects of sofosbuvir (an antiviral drug against chronic HCV) or sofosbuvir combined with ribavirin (an antiviral drug against RNA and DNA viruses) on several biological activities of the body, including hematological, hormonal, biochemical, histological, and immunohistochemical examinations during a long-standing period on male healthy rats. In addition, fertility assessments were performed, including sperm collections and semen parameter investigations. This study was conducted on 21 male rats divided into three equal groups. Group I (control group) received distilled water; group II (sofosbuvir group) received sofosbuvir (4 mg/kg); and group III (sofosbuvir + ribavirin) received sofosbuvir (4 mg/kg) plus ribavirin (30 ml/kg). All groups received the specific drug for six months. Blood and tissue samples were collected for hematological, hormonal, biochemical, histological, and immunohistochemical examinations. In addition, sperm collection and assessments of semen parameters were performed. Results revealed that sofosbuvir causes a highly significant decrease in the mean of most hematological, immunological, hormonal, and biochemical parameters, except for a few numbers of parameters such as neutrophils, monocytes, basophils, cortisol, GOT, and lipase, which exhibit a significant increase. The same occurred in the sofosbuvir + ribavirin group, but at much higher levels, as most hematological, immunological, hormonal, and biochemical parameters exhibit a highly significant decrease except for monocytes, triglyceride, and lipase, which exhibit a significant increase. When compared to the sofosbuvir group alone, the sofosbuvir + ribavirin group demonstrated a highly significant decline in the mean of most hematological, immunological, hormonal, and biochemical parameters except lymphocytes and triglycerides, which exhibit a substantial increase. For the reproductive parameters, both groups exhibit a significant decrease in the total sperm motility percentage. Finally, it can be concluded that sofosbuvir causes acute pancreatitis and combined immunodeficiency. Ribavirin is associated with hormonal deficiency, which indicates the occurrence of hypopituitarism. Moreover, sofosbuvir and ribavirin synergistically affect myelosuppression and cause iron-deficiency anemia. However, sofosbuvir, or its combination with ribavirin, is associated with a reduced risk of hepatocellular carcinoma. Besides, adding ribavirin to be combined with sofosbuvir improved the immunodeficiency caused by sofosbuvir; this confirms that using ribavirin with sofosbuvir reduces the side effects of both alone.